Pengaruh The Influence of Occupational Safety and Health on Employee Performance with Work Discipline as a Mediating Variable at PT Vale Indonesia Tbk - Aprilian, Dimas; Subyantoro, Arief; Hikmah, Khoirul (CV. Strata Persada Academia, 2025)
This study aims to analyze the effect of occupational safety and health on employee performance with work discipline as a mediating variable at the nickel mining company PT Vale Indonesia Tbk in Sorowako, South Sulawesi. This study uses a quantitative approach with the Structural Equation Modeling (SEM) method with Partial Least Squares (PLS) version 4.0. The population in this study was 2,823 employees of PT Vale Indonesia Tbk in Sorowako, South Sulawesi. The sampling technique used probability sampling with random sampling technique with a sample size of 96 employees working on-site or in the field. The data collection method in this study used a questionnaire measured by a Likert scale. The results showed that occupational safety and health positively and significantly affected employee performance. In addition, work discipline was proven to significantly mediate the relationship between occupational safety and health and employee performance. The implications of this study are to emphasize the importance of implementing good OHS and high work discipline in improving employee performance, as well as providing recommendations for company management to continue strengthening OHS policies and work discipline to achieve optimal performance.